Socio-cultural Adaptation of Children of Migrants In the Process of Ethnographic Tourism - Kilichenko, Oksana; Vovchok, Yaroslav (Journal of History Culture and Art Research, 2019)
The article examines the conditions and directions of socio-cultural adaptation of migrant- children in the process of ethnographic tourism. The terms "migration", "socio-cultural adaptation", "social activity", "ethnographic tourism" are specified. The peculiarities of socio-cultural adaptation of pupils of different nationalities in elementary school in the western region of Ukraine are described. The stages of socio-cultural activity defined by V. Ruthen and M. Koksien are specified in accordance with the conditions of the elementary school. The influence of factual and virtual ethnographic tourism on the formation of children's status is researched. It is noted that in the conditions of organization of educational process in primary school virtual tourism is more often used. Requirements for using virtual tours, oral journals, projects in the process of socio-cultural adaptation of migrant- children are analyzed, and the features of how to conduct these activities with children from 6 to 10 years old are presented. The main thing about using virtual ethnographic tourism is that children not only get acquainted with and adapt to a new socio-cultural environment, but also introduce classmates to their native socio-cultural setting. The role of factual tourism, the main task of which is to get acquainted with culture, everyday life, traditions, dialects, cuisine, and applied art is analysed. For this purpose, teachers use excursions, sightseeing tours in the museums of the city and the region. Schoolchildren were analyzed in order to identify groups of differentiation by level of social activity. The role of official and interpersonal communication in the development of social activity of pupils of junior school age is determined. To monitor the tendencies of interaction between official and unofficial statuses of students and children of migrants in the system of communication and relations in the class, the coordinate - sociogram analysis of the class was used. We used it to observe changes that occur in the groups of attachment and alienation between children aged 6-10 years old in the process of using factual and virtual ethnographic tourism.